Neutral States as Peace Mediators: Favoured or Restrained by Norms?. Issue 4 (31st December 2020) - Goetschel, Laurent
Abstract: Neutral states have traditionally been seen as particularly well suited to function as international mediators. This assessment was based on the fact that both concepts – neutrality and mediation – have their roots in attempts to contain violent conflicts and thereby combine realist and idealistic dimensions of international relations. While due to these normative commonalities, the increased influence of norms in mediation might be deemed to favour the role of neutral states as mediators, a more nuanced analysis reveals a mixed impact: The new norms made mediation enter into policy fields to which neutrality does not apply. But they also increased the complexities of mediation processes which in turn could open up new opportunities for neutral states.